Capacity building program for midwives in maternal mental health through psychoeducation and digital application - Evi Kurniasari Purwaningrum; Alfiesyahrianta Habibie; Siti Khotimah; Sherli Yunita; Afgani Raj Muharman Saputra; Bayu Aji Santoso; Nuryan Ayu (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2025)
Maternal mental health issues are a critical contributor to the high Maternal Mortality Rate in East Kalimantan. Significant challenges in providing adequate support stem from limited psychological services and knowledge gaps among midwives at the Trauma Center Community Health Center (Puskesmas). This community service research aimed to build the capacity of midwives to provide Psychological First Aid (PFA) for pregnant women through a digitally supported psychoeducation program. The methodology involved a psychoeducation program delivered to 30 midwives, featuring a PFA workshop and the socialization of the "Bumil Sejahtera" application. A paired T-test was used to analyze data and measure improvements in participant knowledge and skills. The results demonstrated a statistically significant improvement (p<0.05) across all assessed domains, with the mean score increasing from 87.33 in the pre-test to 113.67 in the post-test. This enhancement of skills is beneficial for the early detection and initial management of maternal mental health issues. For maximum impact, program sustainability is recommended through periodic workshops and collaboration with the local Health Department to expand the application's user reach.